Improving functional performance and muscle power 4-to-6 months after anterior cruciate ligament reconstruction. - Souissi, S.; Wong, D. P.; Dellal, A.; Croisier, J.-L.; Ellouze, Z.; Chamari, K. (Journal of Sports Science & Medicine, 2011)
The purpose of this study was to examine the effects of 8-week retraining programs, with either two or three training sessions per week, on measures of functional performance and muscular power in athletes with anterior cruciate ligament reconstruction (ACLR). Sixteen male athletes were randomly assigned to two groups after ACLR: a functional training group (FTG, n = 8) training 2 intense sessions per week (4hrs/week), and a control group (CG, n = 8) training 3 sessions per week with moderate intensity (6hrs/week). The two groups were assessed at four and six months post-ACLR and the effects of retraining were measured using the following assessments: the functional and the muscular power tests, and the agility T-test. After retraining, the FTG had improved more than the CG in the operated leg in the single leg hop test (+34.64% vs. +10.92%; large effect), the five jump test (+8.87% vs. +5.03%; medium effect), and single leg triple jump (+32.15% vs. +16.05%; medium effect). For the agility T-test, the FTG had larger improvements (+17.26% vs. +13.03%, medium effect) as compared to the CG. For the bilateral power tests, no significant training effects were shown for the two groups in the squat jump (SJ), the counter movement jump (CMJ) and the free arms CMJ (Arm CMJ). On the other hand, the unilateral CMJ test with the injured and the uninjured legs showed a significant increase for the FTG with respect to CG (p < 0.05). The present study introduces a new training modality in rehabilitation after ACLR that results in good recovery of the operated limb along with the contra-lateral leg. This may allow the athletes to reach good functional and strength performance with only two physical training sessions per week, better preparing them for a return to sport activity at 6 months post- ACLR and eventually sparing time for a possible progressive introduction of the sport specific technical training.